#naukanatwitterze. O multimodalnym designie informacji w dyskursie cyfrowym - Makowska, Magdalena (Forum Lingwistyczne, 2020)
The subject of the article are the ways of popularizing scientific and popular science knowledge by using Twitter as a social media platform. The research corpus comprises 100 tweets which come from institutional and individual senders, including both representatives of the world of science as well as of the media that aim to popularize scientific knowledge. As a result of the medialinguistic analysis, which focused on the structural and functional plane of the studied media texts, the high representativeness of multimodal tweets was noted. Namely, language and image contextualize each other: the image allows us to fill the semantic gap resulting from the ellipticalness of the verbal layer of a given tweet. Thus, the contribution of the multimodal information design to knowledge transfer in digital discourse has been demonstrated.